Taraxerol protects the human hepatic L02 cells from hydrogen peroxide-induced apoptosis - Yao, Xiang-Yang; Bai, Qin (Bangladesh Journal of Pharmacology, 2017)
Taraxerol is known to exhibit anti-inflammatory and anti-cancer activity. However, cytoprotective effect of taraxerol on hepatocytes has not been reported. In the present study, we investigated the hepatoprotective effect of taraxerol in the human hepatic L02 cells injured by hydrogen peroxide (H2O2). Taraxerol decreased H2O2-induced cell viability loss and lactate dehydrogenase release. Taraxerol also inhibited H2O2-induced cell apoptosis. Further, taraxerol attenuated H2O2-induced increase in cleaved-caspase-3 and cleaved-PARP. H2O2-activated p38 and JNK were also inhibited by taraxerol. These data suggest that taraxerol could protect the L02 cells against H2O2-induced apoptosis via suppression of p38 and JNK. Taraxerol may be an effective protective agent against oxidative stress-induced liver injury. Video Clip of Methodology: 6 min 20 sec Full Screen Alternate